HUBUNGAN KEMAMPUAN MERANCANG RENCANA PELAKSANAAN PEMBELAJARAN (RPP) DENGAN PRAKTIK MENGAJAR MAHASISWA PRODI PENDIDIKAN GURU SEKOLAH DASAR - Nano Sukmana (Lembaga Penelitian Universitas Langlangbuana, 2020)
This research is motivated by the results of preliminary observations of researchers in the field which show that students of Elementary School Teacher Education Study Programs who will carry out field teaching programs (PPL) in Karang Pawulang State Elementary School Bandung are still having difficulty in making good quality planning tools based on the applicable curriculum. This is evidenced by the results of researchers' interviews with two students who were carrying out PPL who said that they still had difficulty in compiling teaching tools such as the annual program (prota), semester program (promissory notes), syllabus, learning implementation plan (RPP) and so on in accordance with material obtained during lectures on teaching planning and based on the demands of the applicable curriculum. In the implementation of learning, prospective teacher students must have made the necessary learning tools but in their implementation there are still some inappropriate components such as planning tools used in schools. Therefore a research about the relationship between the ability to design teaching planning tools in this case in the form of a lesson plan (RPP) with the practice of teaching PPL students in carrying out learning in elementary schools. This research uses a qualitative approach while this type of research is correlational. In this study, what was investigated was the relationship between the ability to make lesson plans (RPP) and teaching practices in the classroom